MENELAAH KESIAPAN PENCEGAHAN DAN PENANGANAN KEBAKARAN DI LEMBAGA PEMASYARAKATAN KELAS I MADIUN - Kobara Risansaka; Mitro Subroto (Jurnal Komunikasi Hukum, 2022)
Fire is one of the unpredictable disasters, occurring outside of human will and control. The National Disaster Management Agency is an event or series of events that threatens and disrupts people's lives and livelihoods caused by nature or non-natural causes resulting in casualties, whether human, animal, environmental damage, loss, psychological impact. Of course, this fire case still needs to be investigated, considering the number of victims who fell and its location in a correctional institution. The research method used by the author in this article is a qualitative method. Seeing the incident of fire at the Tangerang Class I Lapas, the author was moved to examine the readiness of preventing and handling fires at the Madiun Class I Lapas by making observations at the Madiun Class I Lapas. Based on the research results that have been obtained, it can be seen what are the factors that cause the occurrence of prisons in general. These factors are related to facilitation regarding the age of old buildings, the problem of overcrowding in Correctional Institutions, as well as Standard Operational Procedures in disaster prevention and management in Correctional Institutions. Starting from the fire incident that occurred in the Tangerang Class I Lapas, the Head of the East Java Kemenkumham Regional Office conducted an inspection regarding the facilities and infrastructure at the UPT Corrections in East Java, one of which is the Madiun Class I Lapas (Lapasma). In order to prevent and deal with fires that can occur in Lapasma, various efforts have been made by Lapasma.